Theory of EC processes under steady state conditions at microdisk electrodes: Reversible and irreversible homogeneous kinetics - Barnes, A; Streeter, I; Compton, R (2008)
Finite difference methods are used in conjunction with a quasi-conformal map to simulate an electrochemical process with a coupled reversible first order homogeneous reaction at a microdisk electrode. The dependence of the half-wave potential on the pertinent kinetic and thermodynamic parameters has been investigated and presented on a series of working surfaces. The limiting behavior of the half-wave potential on each working surface is discussed and parametrized where appropriate. The data generated in the investigation has been provided as Supporting Information, allowing the reader to use the results without the need for further calculations. © 2008 American Chemical Society.